A conditionally replication-defective cytomegalovirus vaccine elicits potent and diverse functional monoclonal antibodies in a phase I clinical trial - Li, Leike; Freed, Daniel C.; Liu, Yaping; Li, Fengsheng; Barrett, Diane F.; Xiong, Wei; Ye, Xiaohua; Adler, Stuart P.; Rupp, Richard E.; Wang, Dai; Zhang, Ningyan; Fu, Tong-Ming; et al. (npj vaccines, 2021)
A conditionally replication-defective human cytomegalovirus (HCMV) vaccine, V160, was shown to be safe and immunogenic in a two-part, double-blind, randomized, placebo-controlled phase I clinical trial (NCT01986010). However, the specificities and functional properties of V160-elicited antibodies remain undefined. Here, we characterized 272 monoclonal antibodies (mAbs) isolated from single memory B cells of six V160-vaccinated subjects. The mAbs bind to diverse HCMV antigens, including multiple components of the pentamer, gB, and tegument proteins. The most-potent neutralizing antibodies target the pentamer-UL subunits. The binding sites of the antibodies overlap with those of antibodies responding to natural HCMV infection. The majority of the neutralizing antibodies target the gHgL subunit. The non-neutralizing antibodies predominantly target the gB and pp65 proteins. Sequence analysis indicated that V160 induced a class of gHgL antibodies expressing the HV1-18/KV1-5 germline genes in multiple subjects. This study provides valuable insights into primary targets for anti-HCMV antibodies induced by V160 vaccination.